\[ 4 - 10 = 9 - 15 \] => \[ 2^{2} - 2 \times 2 \times \frac {5}{2} = 3^{2} - 2 \times 3 \times \frac{5}{2} \] => \[ 2^{2} - 2 \times 2 \times \frac {5}{2} + (\frac{5}{2})^{2} = 3^{2} - 2 \times 3 \times \frac{5}{2} + (\frac{5}{2})^{2} \] => \[ ( 2 - \frac{5}{2})^{2} = ( 3 - \frac{5}{2})^{2} \] => \[ 2 - \frac{5}{2} = 3 - \frac{5}{2} \] => \[ 2 = 3 \]

## Comments

Sort by:

TopNewestIf \(x^2=y^2\) then \(\left| x\right|=\left| y\right|\). – Karthik Kannan · 1 year, 10 months ago

Log in to reply